One stage implant-based reconstruction of the breast in a single patient: comparison between mesh and modified dual plane technique - Egidio Riggio; Joseph Ottolenghi; Veronica Grassi; Maurizio Nava (Surgical Techniques Development, 2013)
Acellular dermal matrix and similar meshes are used in breast reconstruction to cover the inferior implant pocket. We considered whether using a modified dual-plane technique in immediate breast reconstruction could improve the outcome when compared with mesh reconstruction. The paper presents a case of a patient who underwent one-stage bilateral immediate breast reconstruction (IBR) with 470 g implants, using alloplastic mesh in one side and the composed dual-plane pocket in the other. In the case described, the composed dual plane technique gave a better result in terms of absence of rippling and smoother surface at the palpation; the mesh coverage gave a better inframammary contour. Our case suggests that the modified dual-plane technique gives a satisfactory cosmetic outcome. It also reduces costs and avoids mesh-related complications. This technique should therefore be considered as an option to the mesh in implant-based breast reconstruction.